Arrhythmic Phenotype of Myocarditis Sustained by a Prominent Infiltration of Conduction Tissue. (August 2019) - Frustaci, Andrea; Verardo, Romina; Grande, Claudia; Galea, Nicola; Chimenti, Cristina
Abstract : Supplemental Digital Content is available in the text.